2022
DOI: 10.3390/polym15010036
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer Gels as a Cleaning System for Differently Featured Wooden Surfaces

Abstract: The cleaning of some wooden artefacts can be challenging due to peculiar surface roughness and/or particular finishing treatments that favour the deposition of dirt and contaminants. The most common cleaning system used by conservators is agar gel, characterized by its rigidity and brittleness, which challenges the cleaning of rough and irregular surfaces typical of most wooden artefacts. In this work, alginate crosslinked with calcium (CA) and konjac glucomannan crosslinked with borax (KGB) gels were proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In Figure 1b, the compressive strength vs. strain profiles of the two specimens are reported. It can be observed that the agar gels and HEMA-MBA/PVP hydrogel were characterized by completely different mechanical behaviors when they were subjected to a uniaxial compressive force: the former showed a fracture zone (peak stress) at low strain values [59], while the latter exhibited a delayed fracture only at the higher level of the considered strain range. Therefore, the agar gel appeared to be more brittle, quickly breaking down, with respect to the HEMA-MBA/PVP hydrogel, which instead showed a longer duration without easy de-structuring [6,[59][60][61].…”
Section: Equilibrium Water Content (Ewc %)mentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 1b, the compressive strength vs. strain profiles of the two specimens are reported. It can be observed that the agar gels and HEMA-MBA/PVP hydrogel were characterized by completely different mechanical behaviors when they were subjected to a uniaxial compressive force: the former showed a fracture zone (peak stress) at low strain values [59], while the latter exhibited a delayed fracture only at the higher level of the considered strain range. Therefore, the agar gel appeared to be more brittle, quickly breaking down, with respect to the HEMA-MBA/PVP hydrogel, which instead showed a longer duration without easy de-structuring [6,[59][60][61].…”
Section: Equilibrium Water Content (Ewc %)mentioning
confidence: 99%
“…It can be observed that the agar gels and HEMA-MBA/PVP hydrogel were characterized by completely different mechanical behaviors when they were subjected to a uniaxial compressive force: the former showed a fracture zone (peak stress) at low strain values [59], while the latter exhibited a delayed fracture only at the higher level of the considered strain range. Therefore, the agar gel appeared to be more brittle, quickly breaking down, with respect to the HEMA-MBA/PVP hydrogel, which instead showed a longer duration without easy de-structuring [6,[59][60][61]. Based on these experimental data as well as the literature data, agar was not considered for the preparation of the emulsion-loaded hydrogels to be applied to the removal of the aged coatings on the stone substrates.…”
Section: Equilibrium Water Content (Ewc %)mentioning
confidence: 99%
“…Our group is also studying the use of konjac, which is also traditionally used in food and cosmetics and can be used for the production of semi-rigid gels. It has already been used to absorb Cu(II) in waste waters in combination with other chemicals [20] and its use in restoration is beginning to be investigated [21]. Therefore, these natural materials can be effective alternatives to agar to improve the cleaning methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is high demand to develop smart cleaning tools that can overcome all these limitations. In recent decades, conservation scientists have investigated alternative products such as physical and chemical gel materials based on natural (e.g., xanthan gum, gellan gum, agar, chitosan, sodium alginate, and glucomannan-borax) and artificial polymers (e.g., polyacrylamide and p(HEMA)/PVP)), as well as conducted research into modifying them to act as a transporting medium for different aqueous cleaning systems (micro-emulsions, mixed solvent systems, micellar solutions, and nanoemulsions), which could be correctly used to clean heritage items and overcome the above-mentioned limitations [16,[23][24][25][26].…”
mentioning
confidence: 99%